PENINGKATAN KOMPETENSI PESERTA DIDIK SMK NEGERI 6 BATAM MELALUI LINK AND MATCH DENGAN DUNIA INDUSTRI DALAM BENTUK KELAS INDUSTRI - Othman, Didel Vianof (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
This research is motivated by the backwardness of the existing curriculum in schools with the current industrial world, this problem is shown by the reality that students who graduate from SMK still have to be retrained at the company where they work so that the industrial world does not get maximum time in terms of accepting new employees This study aims to improve the competence of students through link and match the school curriculum with industry to form an industrial class in the welding engineering department. The results of this study explain that using a link and match school curriculum with industry can improve the skills of students who are already aligned with what the industry wants. It can be proven by the graduates of SMK N 6 Batam in the industrial class already working